1994
DOI: 10.1177/0013164494054002011
|View full text |Cite
|
Sign up to set email alerts
|

Validity Studies the Comprehensive Quality of Life Scale (Comqol): Instrument Development and Psychometric Evaluation on College Staff and Students

Abstract: This article describes the development and validation of a new 35-item, multidimensional Comprehensive Quality of Life Scale (ComQol). Psychometric properties of the scale are described. Consistency between the data yielded by the scale and findings reported in the literature are argued to support the validity of the instrument. It is concluded that ComQol constitutes a unique and comprehensive measure of the quality of life construct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
1
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(126 citation statements)
references
References 7 publications
5
114
1
6
Order By: Relevance
“…It used country averages to reflect aggregate deprivations in health, education and standard of living (UNDP, 1991). Other composite indices that are frequently used or referenced in international literature or in policy include the Physical Quality of Life Index (Morris, 1979), the Quality of Life Index (Dasgupta & Weale, 1992), the Comprehensive Quality of Life Survey (Cummins, McCabe, Romeo & Gullone, 1994), the Combined Quality of Life Indices (Diener, 1995) and the Index of Economic Well-being (Osberg & Sharpe, 2000).…”
Section: Related Literaturementioning
confidence: 99%
“…It used country averages to reflect aggregate deprivations in health, education and standard of living (UNDP, 1991). Other composite indices that are frequently used or referenced in international literature or in policy include the Physical Quality of Life Index (Morris, 1979), the Quality of Life Index (Dasgupta & Weale, 1992), the Comprehensive Quality of Life Survey (Cummins, McCabe, Romeo & Gullone, 1994), the Combined Quality of Life Indices (Diener, 1995) and the Index of Economic Well-being (Osberg & Sharpe, 2000).…”
Section: Related Literaturementioning
confidence: 99%
“…However, recent work has identified some commonly-agreed elements. Cummins et al [4] reviewed 27 definitions of QoL and identified four common components: emotional well-being, health, intimacy issues, and work and productivity [5]. Others have suggested that quality of life is a multidimensional concept incorporating physical and psychological well-being, social participation and lifestyle factors, and an individual's expectations for their life [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Future research should define quality of life more clearly by specifying a comprehensive set of dimensions Vocational Experiences and Quality of Life of Migrants… or components that can truly reflect the connotation of overall life quality. For example, Cummins et al (1994) indicated that quality of life may include such aspects as emotional well-being, intimacy, health, material well-being, safety, and place in society. To ensure the full meaning of quality of life is captured, future empirical research may adopt established measures with sound content validity and psychometrics.…”
Section: Operationalization Of Quality Of Lifementioning
confidence: 99%